Alginate-encapsulated muscle-derived stem cell spheroids promote muscle regeneration in a murine model of volumetric muscle loss - Mitre, Lucas Pari; Ivanov, Giovana Zanetti; Shams, Shahin; Yamaguchi, Fabio; Petraconi, André; Andrade, Ricardo Jorge Espanhol; Silva, Eduardo; Martin, Leonardo; Stilhano, Roberta Sessa (Frontiers in Pharmacology, 2025)
IntroductionVolumetric muscle loss (VML) remains a major clinical challenge due to the limited capacity of skeletal muscle to regenerate large-scale injuries. Muscle-derived stem cells (MDSCs) represent a promising therapeutic option for tissue regeneration; however, their clinical application is constrained by poor post-transplantation viability and limited engraftment. Alginate hydrogels offer a supportive three-dimensional microenvironment capable of encapsulating cells, promoting their survival, and enhancing paracrine signaling through the sustained release of growth factors.MethodsIn this study, we developed and characterized MDSC spheroids and evaluated their regenerative potential when encapsulated in RGD-modified alginate hydrogels. Co-culture with endothelial cells significantly enhanced spheroid viability, indicating beneficial paracrine interactions. To further refine this strategy, 5% of the MDSCs were preconditioned with vascular endothelial growth factor (VEGF) prior to spheroid formation and encapsulation, integrating a pharmacological preconditioning step into the cell–hydrogel platform. Encapsulated spheroids were implanted into a murine model of VML.ResultsAfter 30 days, animals treated with alginate-encapsulated MDSC spheroids containing a 5% VEGF-preconditioned subfraction exhibited reduced granulation tissue, fewer degenerating myofibers, lower fibrosis, and improved early rota-rod performance compared with untreated and scaffold-only controls.DiscussionTogether, these findings highlight a pioneering proof-of-concept platform that combines 3D MDSC spheroids, alginate-based delivery, and VEGF-mediated pharmacological preconditioning for VML repair. As a 100% unconditioned MDSC+alginate group was not included, the present study should not be interpreted as demonstrating in vivo superiority of VEGF preconditioning over unconditioned MDSCs; instead, it provides a rationale for future head-to-head studies explicitly powered to address this question.